Current situation and influencing factors of economic exploitation of the older adult - Li, Kai (Frontiers in Public Health, 2025)
IntroductionAgainst the backdrop of deepening population aging, the issue of economic exploitation among the older adult has become increasingly prominent, severely undermining their financial security and physical and mental well-being. This study aims to investigate the current status of economic exploitation among the older adult, analyze influencing factors such as cognitive function, social support, daily living abilities, and family care, and provide empirical evidence to improve the protection system for the older adults’ rights.MethodsA cross-sectional survey design was employed, selecting 455 older adult individuals from a certain province as the study subjects. Relevant variables were measured using the Mini-Mental State Examination, the Perceived Social Support Scale, the Activities of Daily Living Scale, and the Family Care Index Scale. Statistical analysis methods were used to identify key influencing factors of economic exploitation.ResultsThe survey revealed that the mean score for the Mini-Mental State Examination was 24.40, the mean score for the Perceived Social Support Scale was 53.89, the mean score for the Activities of Daily Living Scale was 32.50, and the mean score for the Family Care Index Scale was 7.89 (p < 0.001*). Older adult individuals in rural areas, with lower education levels, and limited financial resources were at higher risk of economic exploitation.DiscussionThe occurrence of economic exploitation among the older adult is influenced by various factors, including cognitive function, social support, daily living abilities, and family care. To mitigate the risk of economic exploitation, the following measures are recommended: improving cognitive function in the older adult, particularly attention and computational abilities; strengthening the development of family and social support networks; enhancing daily living skills and providing assistance with financial matters; and increasing family care, especially by improving family members’ maturity in handling older adult-related issues. This research provides empirical evidence for formulating strategies to prevent economic exploitation among the older adult, contributing to safeguarding their financial security and improving their quality of life.